Absorption of polycyclic aromatic hydrocarbons onto depolymerized lignocellulosic wastes by Streptomyces viridosporus T7A. Issue 1 (January 2019) - Oliveira, Ana Caroline de; Aguilar-Galvez, Ana; Campos, David; Rogez, Hervé
Abstract: Preparations containing mainly lignified cell walls are effective adsorbents of hydrophobic carcinogens in vitro . Therefore, this innovative study aimed to structurally modify lignocellulosic materials in an enzymatic and environmentally friendly manner to improve the efficiency of sequestering three polycyclic aromatic hydrocarbons (PAHs) by adsorption. Submerged fermentations were performed to produce lignin peroxidase (LiP) in medium supplemented with three different lignocellulosic wastes (0.5% (w/v); açai seed, sugarcane bagasse, and seed coat of Brazil nut), followed by posterior hydrolysis of these three residues and subsequent adsorption to generate hydrolysate wastes. Among the three wastes, the açai seed was the most favourable carbon source for LiP production because a high enzyme activity peak was quickly achieved. Sugarcane bagasse residue was most readily hydrolysed (82.44%), and it had the highest increase in adsorption of the three PAHs tested dissolved in olive oil, from 15.67% of benzo[a]pyrene adsorbed before treatment to 39.45% after treatment. The depolymerisation of wastes may have increased binding sites for olive oil favouring the adsorption of PAHs on hydrolysed residues.